E-Pharmacing and Online Medical Laborotary System - Wilfred P.P.S.; Wanni Arachchige H.S.; Pallewatta U.D.P.; Jayakody J.A.M.G.; D. I. De Silva; Piyumika Samarasekara (International Journal of Engineering and Management Research, 2022)
Pharmacies are not exempt from the changes taking place in the healthcare sector. Web-based application designed to manage tasks in medical laboratories, pharmacies, and the users. It is possible to find the causes and problems of all the illnesses occurring in the customer's body and to perform all the necessary medical tests. Users can get all the details about the available drug counts and inventories using a prescription scanner. There is also an artificial intelligent virtual medical bot providing 24/7 service. Emergency patient can easily learn about the medicine and how to use it and can also know the details needed to contact a nearby hospital. A chat bot is like a virtual human that is used after having a relationship with the user. This study's main goal is to demonstrate how these technologies are employed, as well as their benefits and significance. A new feature introduced here is the creation of a delivery tracking system. This way you can get information about delivery update status from home and can promote a nature friendly environment. A new feature we are introducing here is the creation of a barcode card number by itself. The ccd method is used to create this barcode number.